Social Housing Stock Management toward Sustainable Development Goals in Vietnam: a Case Study of Bac Ninh Province - To Thi Huong, Quynh; Vu Phuong, Ngan; Pham, Thu Phuong (International Journal of Sustainable Construction Engineering and Technology, 2024)
Intending to build one million social housing apartments in the coming time, complete the development of social housing oriented to sustainable development is an important, urgent issue, which plays a decisive role in the development of the social housing stock in Bac Ninh province in particular as well as of Vietnam in general. By field survey method combined with document synthesis, the article has investigated and analyzed the current situation of social housing development in Bac Ninh, and limitations that need to be overcome to harmonize the goal of social housing development with the sustainable development goals of the construction industry. Specific solutions for sustainable development in terms of environment, society and economy, along with the application of 4.0 technology to manage social housing development in Bac Ninh have been researched and proposed.